STUDY OF ANTIMICROBIAL PROTEIN FROM THE HEMOLYMPH OF FRESHWATER CRAB OZIOTELPHUSA SENEX SENEX AND ITS EFFICACY AGAINST THE HUMAN PATHOGENS - D, Sumalatha; Tg, Nithya; J, Jayanthi; Mg, Ragunathan (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The study was done to isolate the antimicrobial protein from the freshwater crab. Methods: Antimicrobial protein was purified by sequential step of ammonium sulfate precipitation, dialysis, ion exchange chromatography, and fast protein liquid chromatography. The apparent molecular mass was determined by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) and matrix-assisted laser desorption ionization-mass spectrometry (MALDI-MS/MS). Primary structure analysis was done from MASCOT search engine. The antimicrobial activity of the protein was done using well diffusion method against Gram-positive and Gram-negative bacteria. Results: The molecular mass of antimicrobial protein was determined to be 33KDa by SDS-PAGE and MALDI-MS/MS. The antimicrobial protein contains eight peptides which were determined by MASCOT search engine. The protein exhibited antimicrobial activity both for Gram-positive and Gram-negative bacteria. Conclusion: The results could provide information for investigating the antimicrobial protein derived from the hemolymph of the freshwater crab Oziotelphusa senex senex.